Outer Membrane Vesicle Induction and Isolation for Vaccine Development - Balhuizen, Melanie D.; Veldhuizen, Edwin J. A.; Haagsman, Henk P. (Frontiers in Microbiology, 2021)
Gram-negative bacteria release vesicular structures from their outer membrane, so called outer membrane vesicles (OMVs). OMVs have a variety of functions, such as waste disposal, communication and antigen or toxin delivery. These vesicles are promising structures for vaccine development since OMVs carry many surface antigens similar to the bacterial surface. However, isolation is often difficult and results in low yields. Several methods to enhance OMV yield exist, but these do affect the resulting OMVs. In this review, our current knowledge about OMVs will be presented. Different methods to induce OMVs will be reviewed and their advantages and disadvantages will be discussed. The effects of the induction and isolation methods used in several immunological studies on OMVs will be compared. Finally, the challenges for OMV-based vaccine development will be examined and one example of a successful OMV-based vaccine will be presented.